Thermal time for reproductive phenological stages of pineapple guava (acca sellowiana (o. berg) burret) (2015)
Crop development of feijoa (Acca sellowiana (O. Berg) Burret) is mainly stimulated by temperature, but is also affected by other climatic factors. The determination of the development in terms of thermal time or growing degree days (GDD) is more precise than calendar days. The aim of this study was to propose a phenological model for feijoa cv. Quimba, in which the base temperature (Tb) for four different phenological stages and its duration in terms of GDD is estimated to predict the timing of anthesis, fruit setting and harvesting. During the years 2012 to 2014, in two localities of the department of Cundinamarca, Colombia, twenty trees per farm were labeled, dates of occurrence of phenological stages, starting from floral button were recorded. Tb was estimated using the method of minimum coefficient of variation, as well as duration of the four reproductive phenological stages in terms of GDD. The results showed that Tb and GDD vary depending on the stage of development of the crop; in general, an average of 2651 GDD and 189 days is required to reach the flower bud to the fruit harvest. The parameters of the regression analysis showed that the model successfully predicted phenological stages when estimated Tb for each of them was used, with high determination coefficient. Cross-validation showed good statistical fit between predicted and observed values; intercept was not significantly different from zero (p 0.05) and the slope was statistically equal to oneTIEMPO TÉRMICO PARA ESTADOS FENOLÓGICOS REPRODUCTIVOS DE LA FEIJOA (Acca sellowiana (O. Berg) Burret)El desarrollo del cultivo de feijoa (Acca sellowiana (O. Berg) Burret) es principalmente estimulado por la temperatura, pero también es afectado por otros factores climáticos. La determinación del desarrollo en términos de tiempo térmico o grados día de crecimiento (GDC) es más precisa que en días calendario. El objetivo de este estudio fue proponer un modelo fenológico para la feijoa cv. Quimba, en el que se estima la temperatura base (Tb) para cuatro períodos fenológicos reproductivos diferentes y su duración en términos de GDC, para predecir las fechas de antesis, cuaje de fruto  y cosecha. Se marcaron veinte árboles por finca en dos localidades del departamento de Cundinamarca, Colombia, durante los años 2012 a 2014, se registraron las fechas de aparición de los estados fenológicos, desde la formación del botón floral. Se estimó Tb usando el método de mínimo coeficiente de variación, así como la duración de los cuatro estados fenológicos reproductivos en términos de GDC.  Los resultados mostraron que Tb y GDC varían dependiendo de la etapa de desarrollo del cultivo; en general, se requiere una media de 2651 GDC  y 189 días para llegar de botón floral a la cosecha del fruto. Los parámetros del análisis de regresión mostraron que el modelo predijo satisfactoriamente las etapas fenológicas cuando se usó la Tb estimada para cada una de ellas, con alto coeficiente de determinación. La validación cruzada mostró buen ajuste estadístico entre valores pronosticados y observados; la intercepción no fue significativamente diferente de cero (p 0,05) y la pendiente fue estadísticamente igual a uno.